Player position relationships with centrality in the passing network of world cup soccer teams: Win/loss match comparisons. (April 2020) - Clemente, Filipe Manuel; Sarmento, Hugo; Aquino, Rodrigo
Abstract: Among elite national soccer team play of the 2018 FIFA World Cub, we analyzed (a) network centrality variations between playing positions during passing sequences, and (b) their relationship to match outcomes. We observed and coded the 64 matches played by 32 teams and collected passing distribution data between teammates. We then converted it into adjacency matrices to calculate passing network data. We found large decreases in degree prestige (inbound pass links) among players in winger positions compared to external defenders (−41.8%; ES (effect size): −1.79). Large decreases in degree prestige were also found in central forwards in comparison to external defenders (−38.7%; ES: −1.62), central defenders (−42.3%; ES: −1.60), defensive midfielders (−47.1%; ES: −1.87) and midfielders (−40.8%; ES: −1.59). Comparisons of passing network centrality levels between won and lost matches revealed small increases in degree prestige among midfielders (17.4%; ES: 0.31) and small increases among forwards (33.9%, ; ES: 0.53) among matches won. Thus, match outcome (and possibly scoring status during the match) was somewhat related to the passing network centrality of various playing positions during passing sequences.